Pembatasan Pernikahan Ditinjau Dari Psikologi - Muhammad Zainuddin Sunarto; Fathor Rozy (Universitas Mataram, 2022)
This study aims to reduce the occurrence of marriage at an early age. This research uses a normative approach method by examining the results of previous researchers. Adolescence is an age that bridges between the ages of children and adults. In adolescence, there are many changes that are not easy for a child to deal with, of course, they need help and protection from parents and adults. The development in the era of technology, it is very easy for teenagers to fall into free struggle and not a few teenagers who choose to get married at an early age. In a relationship, marriage becomes a very natural thing to do without thinking about what will be faced afterwards. Many problems occur in a couple after marriage, especially at an early age, because there is no prior readiness. In mental readiness that is often underestimated can have a bad impact on family members. Divorce is often preceded by various conflicts caused by a lack of psychological readiness in the face of marriage. Therefore, researchers conducted research related to mental weakness in adolescence and what things need to be prepared before marriage so as not to bring harm to the family.